2021
DOI: 10.1038/s41598-021-85222-5
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia cenocepacia transcriptome during the early contacts with giant plasma membrane vesicles derived from live bronchial epithelial cells

Abstract: Burkholderia cenocepacia is known for its capacity of adherence and interaction with the host, causing severe opportunistic lung infections in cystic fibrosis patients. In this work we produced Giant Plasma Membrane Vesicles (GPMVs) from a bronchial epithelial cell line and validated their use as a cell-like alternative to investigate the steps involved in the adhesion process of B. cenocepacia. RNA-sequencing was performed and the analysis of the B. cenocepacia K56-2 transcriptome after the first contacts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Previous work has shown that BCAM2418 gene is upregulated upon bacterial contact with host cells, reaching a maximum level of expression after 30 min of adhesion Pimenta et al, 2021). This indicates a fine-tuned regulation event that seems to function in the early steps of infection and may derive from cross-talk between the bacterium and O-glycosylated host cell surface components .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous work has shown that BCAM2418 gene is upregulated upon bacterial contact with host cells, reaching a maximum level of expression after 30 min of adhesion Pimenta et al, 2021). This indicates a fine-tuned regulation event that seems to function in the early steps of infection and may derive from cross-talk between the bacterium and O-glycosylated host cell surface components .…”
Section: Discussionmentioning
confidence: 80%
“…BCAM2418 is one of the largest TAAs, comprising 2,775 amino acids and exhibiting a high proportion of serine residues consensus motifs distributed across its extracellular passenger domain (Mil-Homens & Fialho, 2011). We recently described that the expression of BCAM2418 requires physical contact between bacteria and epithelial host cells and displays a fine-tuned control during time and is particularly relevant in the early stages of infection Pimenta, Bernardes, Alves, Mil-Homens, & Fialho, 2021). Moreover, we found that the surface exposed head-stalk domains of BCAM2418 mediates bacterial binding to O-linked glycans conjugated to host cell-surface mucins .…”
mentioning
confidence: 99%
“…Pimenta et al observed that the expression levels of genes involved in sulfur metabolism are up-regulated by REs. These molecular changes reportedly occur during the early stage of the adhesion of pathogenic B. cenocepacia K56-2 to the host cell giant plasma membrane vesicles (GPMVs) derived from live bronchial epithelial cells [ 26 ]. The assimilation of sulfur from inorganic sulfate and other sources seems to be a rapid response of B. cenocepacia to the initial interactions with the host [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Pimenta et al observed that the expression levels of genes involved in sulfur metabolism (e.g., genes related to sulfur transport, sulfate activation and reduction, and sulfonate transport) are up-regulated by REs. These molecular changes reportedly occur during the early stage of the adhesion of pathogenic B. cenocepacia K56-2 to the host cell giant plasma membrane vesicles (GPMVs) derived from live bronchial epithelial cells [33]. The assimilation of sulfur from inorganic sulfate and other sources seems to be a rapid response of B. cenocepacia to the initial interactions with the host [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the ywkA expression level in strain P10 was up-regulated by 1.56fold (Table 2). Moreover, a 30-min incubation with GPMVs suppresses the expression of B. cenocepacia genes involved in the chemotaxis signaling pathway, whereas the iC, gK, motA, and mcp expression levels are down-regulated upon adhesion [33]. Plant-microbe interactions are highly complex.…”
Section: Discussionmentioning
confidence: 99%